EVALUASI KEGIATAN PROMOSI PERPUSTAKAAN UMUM (STUDI KASUS PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA DENPASAR) - Afriadinatha, I Putu Doddy; Kastawa, Made; Ginting, Richard Togarata (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2018)
ABSTRACT The purpose of this research is to find out how the promotion activities of Dinas Perpustakaan dan Kearsipan Kota Denpasar by using descriptive qualitative research metodh. Sources of data in this research comes from observation, interview, documentation dan literature study. In performing data analysis techniques, the authors use data reduction stages, data presentation and drawing conclusions. The results of this study indicate that the promotion activities of the Dinas Perpustakaan dan Kearsipan Kota Denpasar using promotional media, such as leaflet, website, advertising media, technical guidance, mobile libraries and exhibition. Based on interview from informants, mobile libraries and exhibitions are the most effective media to promote library. The obstacles when doing the promotion activities, Dinas Perpustakaan dan Kearsipan Kota Denpasar have any internal and external factor. Keywords: Library promotion, Promotion strategy, Promotion media